JIRA 7 administration cookbook : over 80 hands-on recipes to help you efficiently administer, customize, and extend your JIRA 7 implementation /: over 80 hands-on recipes to help you efficiently administer, customize, and extend your JIRA 7 implementation. (2016) - Li, Patrick, 1983-
No abstract available